"Breast abscess in a male patient due to Finegoldia magna and Bifidobacterium scardovii: An unusual entity". (June 2022) - Sunil Krishna, M.; Shenoy, Padmaja Ananth; Priyanka, Kocherlakota Sathya; Vishwanath, Shashidhar
Abstract: Breast abscess in men is a very uncommon condition. Unlike females, breast abscesses in men are commonly caused by aerobic organisms and very rarely by anaerobes. We are hereby reporting a case of retro-areolar abscess in a male patient caused by anaerobic organisms. The culture of the drained abscess yielded the growth of Finegoldia magna, a strict anaerobic Gram-positive cocci, and Bifidobacterium scardovii, a slow growing non spore-forming anaerobic Gram-positive bacilli. Timely surgical intervention and initiation of appropriate antimicrobial therapy showed an improvement of this condition. Highlights: Breast abscess in men is a very rare entity. We present a case of breast abscess in a male patient caused by anaerobic bacteria. Finegoldia magna is a well-recognized pathogen in diverse clinical infections. Bifidobacteria are the important part of gut microbiota and are often neglected in clinical specimens. The microbiological workup for cases of breast abscesses should include both aerobic and anaerobic cultures.